Study on the contamination rate of traditional white cheese presented in Tabriz Markets to coliforms and pathogenic Escherichia coli - M Pourali-Behzad; H Mirzaei (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2011)
Coliforms are considered as hygienic indicator organisms in foodstuffs and Escherichia is one of its genera. Escherichia coli is the most important species of the genus Escherichia and generally is considered as part of natural bacterial flora of human and most animals intestine. Pathogenic Escherichia coli is causative agent of diarrhea in developing countries and areas with poor hygienic condition. The purpose of this study was to investigate the contaminated status of traditional white cheese in Tabriz retails in terms of coliforms, faecal coliforms, Escherichia coli, and pathogenic Escherichia coli. Ninety samples of white cheese were randomly collected from retails of different part of Tabriz. The samples were transferred to the laboratory under refrigerated conditions. Coliforms were counted by means of VRBA with pour plate method at 37±1°C. For Faecal Coliforms Briliant Green Bile broth at 44±0.5 °C were used. For confirming Escherichia coli among coliform bacteria, IMViC tests were applied. Pathogenic Escherichia coli was distinguish by polyvalent antiserums. The results of the study indicated that, the mean of coliforms were estimated at (27.07±1.51) ×105 cfu/ml. The number of coliforms in 88 (98%) samples  was more than the limit allowed by the national standard for Iranian industrial white ripened cheese. Moreover, Sixty-three (70%) of the samples were contaminated to faecal coliforms. Although, 11 (12%) of the samples were contaminated to Escherichia coli, any sample was contaminated to pathogenic Escherichia coli. It can be concluded that, hygienic status of traditional white cheese offered in Tabriz markets was not satisfactory in terms of contamination to coliforms and Escherichia coli is. However, no samples was found positive as pathogenic Escherichia coli.